Legal Control Efforts Against Illegal Buildings on the Borders of the Pelayaran River (Indonesian Journal of Agrarian Law, 2026)
Spatial planning in river border areas is an essential instrument for maintaining the ecological function of rivers and ensuring land use complies with applicable laws and regulations. However, the implementation of legal control over illegal buildings along the Pelayaran River border in Karangtowo Village, Demak Regency, continues to face various obstacles, preventing effective enforcement. This study aims to analyze the implementation of legal control over illegal buildings based on the Regulation of the Minister of Public Works and Public Housing Number 28/PRT/M/2015 and to identify the factors hindering its effectiveness. This research employed an empirical juridical method with a qualitative approach. Data were collected through field observations, interviews with relevant government agencies and local communities, and a review of legislation and related literature. The findings indicate that legal control has not been implemented optimally. Normatively, the Pelayaran River is classified as an urban river without embankments, requiring a minimum river border distance of ten meters from both sides of the riverbank. Empirically, approximately seventy semi-permanent buildings are still used for commercial purposes, with several structures extending into the river channel, violating the Ministerial Regulation. This condition reflects a gap between das sollen and das sein in spatial control implementation. Major obstacles include low public legal awareness, ineffective public outreach, the high economic value of the river border area, and increasing commercial activities driven by nearby industrial development. Strengthening institutional coordination, continuous monitoring, and community empowerment are therefore necessary to restore the river border's protective function sustainably.